NHC-catalysed aerobic aldehyde-esterifications with alcohols: no additives or cocatalysts required - CONNON, STEPHEN (My University, 2013)
A highly efficient, broad scope, additive-free mild protocol for the oxidative carbene-catalysed esterification of aldehydes (including the related aqueous oxidation to acids) has been developed
PUBLISHED
Keywords: Chemistry